Preliminary assessment of the shared service facilities - Erlinda M. Medalla; Fatima Lourdes Del Prado; Melalyn C. Mantaring; Angelica B. Maddawin (Philippine Institute for Development Studies (PIDS), 2016)
This paper assesses one of the pillars of the "Big Push" for micro, small, and medium enterprise (MSME) development of the Department of Trade and Industry (DTI): the shared service facility (SSF). Implemented in 2013, SSF seeks to address the gaps and bottlenecks in the value chain of priority industry clusters through the provision of processing and/or manufacturing machinery, equipment, tools, and related accessories for the common use of MSMEs. The assessment used case studies of selected three project sites where focus group discussions (FGDs) were held and preliminary data on output, performance, and costs could be obtained. Overall data from DTI on SSF were also utilized. The results appear promising, although still not robust enough because of insufficient data, and the program being still in early stage (2nd year) of implementation. The project costs very little, but it has had notable and substantial impact on jobs and productivity. This is indicated by the low estimates of the implicit subsidy per worker and generally favorable measure of the benefit-cost ratio of projects undertaken under the program. In addition, the FGDs, on the whole, brought out encouraging feedback from all concerned.
Keywords: 330; Shared Service Facility; Micro Small Medium Enterprises; SME Development